2019
DOI: 10.1111/ggi.13601
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and affect balance of empty‐nest older adults with mild cognitive impairment in poor rural areas of Hunan province, China

Abstract: Aim To evaluate the prevalence of mild cognitive impairment (MCI) within the empty‐nest older adults population in poor rural areas of the Hunan province of China, and to explore the effects of resilience and affective balance on cognitive functioning within this specific population. Methods A cross‐sectional, multistage, random cluster survey was administered to participants from March 2013 to December 2014 in the Hunan province. There were a total of 1164 participants. These participants were empty‐nest olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
1
9
1
1
Order By: Relevance
“…The findings also revealed that affect balance acted as a mediator of the association between resilience and perceived stress, which is in line with previous studies that SUD patients with a high perception of social support are prone to show more resilience (44). Precious studies suggest that those with higher resilience are more likely to experience higher affect balance (55), which in turn decreases perceived stress (56). The theoretical underpinning of the current findings is that different dimensions of perceived social support may promote resilience, while resilient individuals are good at balancing their affections, ultimately reducing stress perception.…”
Section: Discussionsupporting
confidence: 90%
“…The findings also revealed that affect balance acted as a mediator of the association between resilience and perceived stress, which is in line with previous studies that SUD patients with a high perception of social support are prone to show more resilience (44). Precious studies suggest that those with higher resilience are more likely to experience higher affect balance (55), which in turn decreases perceived stress (56). The theoretical underpinning of the current findings is that different dimensions of perceived social support may promote resilience, while resilient individuals are good at balancing their affections, ultimately reducing stress perception.…”
Section: Discussionsupporting
confidence: 90%
“…With regards to resilience, growing literature demonstrates that resilience is a significant predictor of meaningful living (Kleiman, & Beaver, 2013), psychological distress, subjective well-being, and quality of life (Tecson, Wilkinson, Smith, & Ko, 2019), affect balance, life satisfaction, and psychosocial well-being, and decreased negative affect (Yildirim, 2019), moods, depression, and anxiety (Burns, Anstey, & Windsor, 2011). Furthermore, resilience mediates the relationship affect balance and cognitive impairment (Xie, Zhou, Deng, Richmond, & Na, 2019). Within the context of COVID-19, a recent study showed that resilience had a significant direct effect on subjective well-being and psychological health among general public during early phase of COVID-19 (Yildirim, & Arslan, 2020).…”
Section: Affective Balance Resilience and Psychological Healthmentioning
confidence: 99%
“…Dentro do atual cenário contemporâneo urbano, em que se têm diversas relações e diversos tipos de família, o sistema heteronormativo contribui para a SNV, no sentido literal da palavra. A mãe e o pai, tendo um ao outro, torna a saída do filho e os sentimentos que a situação traz ainda mais ressaltados 27 . Eram pais que cooperaram juntos para o crescimento de um filho e que agora se veem sem ele.…”
Section: No Presente Estudo Após Avaliados Os Resultados E Analisados...unclassified